STRATEGI PENINGKATAN MUTU PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR MELALUI PENJAMINAN MUTU BERKELANJUTAN - Sal Shakhiba Albira Nanda Hanafi Salsha; Romi Faslah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
ABSTRACT Learning of Islamic Religious Education (PAI) in elementary schools plays a crucial role in shaping students’ character and spirituality. However, the implementation of PAI learning still faces various challenges, such as the low effectiveness of learning processes, limited teacher competence, and the suboptimal application of quality assurance systems at the elementary school level. This article aims to analyze strategies for improving the quality of PAI learning through a continuous quality assurance approach. This study employs a literature review method by examining various scholarly sources, including books, journals, and educational policies related to improving the quality of religious learning. The findings indicate that the quality of PAI learning can be enhanced through the application of a continuous quality assurance cycle (Plan-Do-Check-Act). The main strategies include contextual lesson planning, innovative implementation based on Islamic values, continuous evaluation, and follow-up actions to strengthen teacher professionalism. The conclusion of this study emphasizes that the success of improving PAI learning quality depends on the synergy between managerial, pedagogical, and spiritual aspects in the implementation of a sustainable quality assurance system. The implications highlight the need to strengthen the roles of teachers and educational institutions in consistently applying a culture of quality so that PAI in elementary schools can produce a generation that is virtuous, faithful, and adaptive to contemporary developments.